Understanding the marketing exceptionality of prestige perfumes - Horoszko, Nithda; Moskowitz, David; Moskowitz, Howard R. (Routledge, 2018)
Women have an affinity with the brand of perfume they wear. People often hold strong emotional connections to different scents, such as their mother's perfume or the body spray they wore as a teen. Despite huge marketing budgets, the launches of established brands often fail, despite extensive marketing research and lavish resources. Why is this? This text is a first in the field to recognize that fine fragrance cannot be treated as any other product. With case studies from Jill Sander, Estee Lauder and Dior, this book debunks the classic marketing techniques which often hinder the success of new perfumes. Authored by two leading market researchers, this study analyses the 'five great brands' of the perfume industry and demonstrates how to value perfume lines according to 'brand DNA'. This ground-breaking book will provide students with all the tools of a successful practitioner in the perfume industry. Understanding the Marketing Exceptionality of Prestige Perfumes will prove to be a vital text for any student, specialist or practitioner of luxury marketing looking to understand the fine fragrance market.